Effects of Anti-Black Political Messages on Self-Esteem. Issue 1 (25th March 2015) - Lyle, Monique L.
Abstract: This study examines how anti-Black political rhetoric affects race-specific collective self-esteem (R-CSE) and internal political efficacy among African–Americans and Whites. Results from an experiment in which subjects received an anti-Black stereotype-accentuating message attributed to either a political figure or an "ordinary American, " or no message at all, demonstrate that the political message undermined how African–Americans regard their own racial group, activated beliefs about how others regard African–Americans as a predictor of how African–Americans regard their own racial group, and undermined internal political efficacy. For Whites, the results demonstrate that the political message moderated the relationship between how they regard their own racial group and beliefs about how others regard their racial group, though the political message did not significantly increase or decrease racial group-regard or political efficacy overall. These results provide empirical confirmation of the role that government and politics can play in self-esteem.